Novel textile systems for the continuous monitoring of vital signals: design and characterization - Trindade, Isabel G.; Martins, Frederico; Dias, Ruben; Oliveira, Cristina; Machado da Silva, Jose (2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2015)
In this article we present a smart textile system for the continuous monitoring of cardiorespiratory signals, produced and integrated with an industrial embroidery unit. The design of a T-shirt system, having embedded textile sensors and interconnects and custom designed circuit for data collection and Bluetooth transmission is presented. The performance of skin-contact textile electrodes, having distinctive electrical characteristics and surface morphologies, was characterized by measurements of signal to noise ratio, under dry and moisture conditions. The influence of the electrodes size and the wear resistance were addressed. Results of an electrocardiogram acquisition with a subject wearing the T-shirt and display on a smartphone are also shown. The presented smart textile systems exhibit good performance and versatility for custom demand production.